Böbreküstü Bezleri (Annals of Medical Research, 1977)
In this study, classical knowledge and recent literature related to embryological development and both macroscopic and microscopic structures of the adrenal were glands reviewed.
Keywords: Adrenal glands; anatomy; histology; embryology